Spiritual Meaning-Making and Collegial Solidarity in Sustaining Teacher Resilience - Pasaribu, Udur Maulina Manjur; Erny, Erny (Mitra Edukasi dan Publikasi, 2026)
Teacher well-being has gained attention in educational research because increasing professional demands and institutional pressures have amplified teachers’ experience of work-related stress. This study sought to explore the perceptions of elementary school teachers about occupational stressors, how they experience and manage occupational stressors, and the extent to which these coping mechanisms contribute to their professional resilience. Data were obtained through a qualitative interpretive case study design through semi-structured interviews, classroom observations, and document review of eleven teachers with differing years of experience. Data were analyzed with the aid of Miles and Huberman’s interactive model, including the stages of reduction of data, display, and verification through triangulation and member checking. The results showed that teachers’ stress is largely due to administrative overload, lack of resources, and performance pressure. Yet, rather than causing burnout, many teachers found resilience in stress as they engaged in spiritual reflection, collegial collaboration and supportive infrastructure. These coping strategies were effective in maintaining emotional stability, professional ethics, and commitment/motivation toward teaching. The study illustrates how faith-based and community-oriented coping is an important culture-embedded coping tool that may aid in teacher wellness and support in challenging environments. The research thus sheds light on how teachers turn stress into professional growth. The results emphasize the significance of supportive school climates and holistic well-being programs, drawing on psychological, spiritual and social domains, for enhancing teacher strength of resilience and performance.